Guided Discovery Learning Using Andromatics Tables to Improve Motivation and Mathematics Learning Outcomes - Nurohim, Nurohim (Jurnal Didaktika Pendidikan Dasar, 2021)
Learning outcomes that are not optimal can cause delays in further learning. The discovery learning research objective is to develop ICT-based learning media, namely the Andromatics Table which is applied to guided discovery learning and to know its effects on increasing motivation, learning outcomes, and describing the characters developed in the implementation of Mathematics learning. The research uses the 4D (Four-D) model research and development method which includes defining, design, develop, and disseminate. The results showed a significant increase in the motivation, learning outcomes, and character of IVB grade students at Kaliwlingi State Elementary School 02. Based on the ARCS questionnaire instrument, students’ learning motivation increased by 26 students, which initially averaged less than average be very good. The learning outcomes of students whose initial percentage of mastery learning was only 38.46% while after the action percentage of completeness became 96.15% within an average value of learning outcomes reaching 89,62. Mathematics KKM is 65. The character of students that increases after learning based on the PPK movement includes the value of self-reliance, mutual cooperation value, and integrity values. The conclusion can be drawn that Guided Discovery Learning using the Andromatika Table has an impact on increasing motivation, learning outcomes, and developing students’ character.